Filosofia dell’incertezza. Su un appunto del giovane Kafka (Materiali di Estetica. Terza serie, 2017)
The paper analyses one of Kafka’s earliest texts by contextualising its philosophical discourse in connection with the teaching of philosophy in contemporary Prague. It starts by referring to Brentano’s supposedly influence on Kafka and it moves on by discussing Max Brod’s tumultuous relation with the Prague Brentanist circle. Kafka’s and Brod’s participation to the Café Louvre philosophical meetings and to the Fanta Salon is also taken into consideration. Finally, the contribution tries to relate Kafka’s fragment to one of its earliest stories: Description of a Struggle (Beschreibung eines Kampfes).Keywords: Franz Kafka; Franz Brentano; Max Brod; Fanta Circle; Anton Marty